Globalization in History: A Geographical Perspective. - Crafts, N; Venables, A (CEPR, 2001)
This Paper argues that a geographical perspective is fundamental to understanding comparative economic development in the context of globalization. Central to this view is the role of agglomeration in productivity performance; size and location matter. The tools of the new economic geography are used to illuminate important episodes when the relative position of major economies radically changed: the rise of the United States at the beginning and of East Asia at the end of the 20th century. It is suggested that while lack of high quality institutions has been a major reason for falling behind geographic disadvantages also merit attention.